The effects of Phycocyanobilin on experimental arthritis involve the reduction in nociception and synovial neutrophil infiltration, inhibition of cytokine production, and modulation of the neuronal proteome - Marín-Prida, Javier; Rodríguez-Ulloa, Arielis; Besada, Vladimir; Llopiz-Arzuaga, Alexey; Batista, Nathália Vieira; Hernández-González, Ignacio; Pavón-Fuentes, Nancy; Marciano Vieira, Érica Leandro; Falcón-Cama, Viviana; Acosta, Emilio F.; Martínez-Donato, Gillian; Cervantes-Llanos, Majel; et al. (Frontiers in Immunology, 2023)
The antinociceptive and pharmacological activities of C-Phycocyanin (C-PC) and Phycocyanobilin (PCB) in the context of inflammatory arthritis remain unexplored so far. Here we aimed to assess the protective actions of these compounds in an experimental mice model that replicates key aspects of human rheumatoid arthritis. Antigen-induced arthritis (AIA) was established by intradermal injection of methylated bovine serum albumin in C57BL/6 mice, and one hour before the antigen challenge, either C-PC (2, 4 or 8 mg/kg) or PCB (0.1 or 1 mg/kg) were administered intraperitoneally. Proteome profiling was also conducted on glutamate-exposed SH-SY5Y neuronal cells to evaluate the PCB impact on this key signaling pathway associated with nociceptive neuronal sensitization. C-PC and PCB notably ameliorated hypernociception, synovial neutrophil infiltration, myeloperoxidase activity, and the periarticular cytokine concentration of IFN-, TNF-, IL-17A and IL-4 dose-dependently in AIA mice. In addition, 1 mg/kg PCB downregulated the gene expression for T-bet, ROR, and IFN- in the popliteal lymph nodes, accompanied by a significant reduction in the pathological arthritic index of AIA mice. Noteworthy, neuronal proteome analysis revealed that PCB modulated biological processes like pain, inflammation, and glutamatergic transmission, all of which are involved in arthritic pathology. These findings demonstrate the remarkable efficacy of PCB in alleviating the nociception and inflammation in the AIA mice model and shed new light on mechanisms underlying the PCB modulation of the neuronal proteome. This work opens a new avenue to explore its translational potential for developing a therapeutic strategy for inflammation and pain in rheumatoid arthritis.